Beyond the medals: a cross-sectional study exploring retired elite female athletes` health - Thornton, J.; Rosen, C.; Davenport, M.; Mountjoy, M. L.; Dorian, P.; Gouttebarge, V.; Breau, B.; Pila, E.; Reilly, K.; Yuan, J.; Mok, K.; di Ciacca, S.; et al. (BMJ Open Sport & Exercise Medicine, 2023)
Objectives: Little is known about the impact of elite sport participation on long-term athlete health. We aimed to: (1) describe musculoskeletal, mental health, reproductive/endocrine and cardiovascular characteristics in retired elite female athletes and compare to the general population and (2) explore athletes` perceptions of their elite sport participation and its impact on health.